MOVEMENTS OF WATER IN CELLS OF NITELLA - Osterhout, W. J. V. (The Rockefeller University Press, 1949)
When one end of a Nitella cell (A) is bathed in water and a solution of sucrose is placed at the other (B) we find that water enters at A, travels along inside the cell, and escapes at B. The solutes which cannot pass out through the protoplasm at B remain behind so that the osmotic pressure increases at B and diminishes at A until equilibrium is reached and the motion stops. An equation is given which enables us to predict with considerable accuracy the amount of flow required to produce equilibrium.